‘Feudalism’ and the Boyars of Medieval Russia - Stephanovich, Petr Sergeyevich (Dějiny – teorie – kritika, 2008)
Th e article considers with the question of ‘Russian feudalism,’ that is, the applicability of the concept of feudalism to medieval Russian society. A detailed historiographic overview is provided to show how, from the late eighteenth century to the present, various scholars compared Russian and European historical approaches to feudalism. The author shares Aron Gurevich’s scepticism about the heuristic value of applying the ‘feudal model’ to describe medieval European society and he shows the limited applicability of the model to old Russian nobility, the boyars. In medieval Russia, the nobility’s unity, supreme status, and access to institutionalized power were ensured by rather different factors not directly related to feudal institutions. These factors include the unique ethos of the relationships between the nobility and the sovereign as well as their joint ceremonial meals/feasts and military ventures. It is the comparative study of such ‘nodes of an interpersonal network’ (as Gurevich put it) that will help us to better understand the shared and particular features of the various patterns of social development in different regions of medieval Europe.